Circadian aspects of mortality in hospitalized patients: A retrospective observation from a large cohort - Miao Fang; Shunju Xiang; Xiaoqiang Xiao; Qianning Mo; Yang Si (Wiley, 2023)
Abstract Aim This study aimed to describe the circadian characteristics of hospitalized mortality in order to provide nursing guidance for preventing in‐hospital mortality. Design A retrospective analysis on inpatient information was implemented. Methods Harmonic Analysis of Time Series was applied to quantify the periodic structure of the frequency of the occurrence of death. Results A total of 3300 cases were included in the present study (male, 63.4% and median age 73 years), including 1540 (46.7%) ICU patients. Incidence of overall hospitalized death exhibited a circadian pattern, presenting peaks from 07:00 to 12:00 and 15:00 to 20:00 P.M., with 21.5% and 13.1% increase above the average at those peak points, respectively. Similarly, the incidence of sudden cardiac death (SCD) showed peaks between 06:00-12:00 and 15:00-20:00, with a 34.7% and 28.0% increase above the average at peak time, respectively. The distribution of death incidence revealed no statistical difference between SCD and non‐SCD (p = 0.525).